Analisis Nilai Tambah Komoditas Unggulan Subsektor Perkebunan - Dahiri Dahiri (Pusat Kajian Anggaran, 2022)
Plantation commodities contribute to the national economy which is reflected in their large contribution to the gross domestic product, employment, and the trade balance which is always positive. However, exports of plantation commodities are very much dominated by fresh or intermediate products. This shows that the added value of plantation commodity products is still low. The research model used is qualitative research. The results showed that the low added value was caused, namely, first, the plantation industry still focused on producing fresh or intermediate products. Second, the mismatch between upstream and downstream plantations. Third, the lack of regulations to prohibit the export of plantation products in fresh or intermediate form. Departing from these problems, the government needs to first, the provision of Physical Plantation Special Allocation Funds for local governments and incentives for the plantation industry. Second, increasing the productivity and quality of smallholder plantation products. Third, the urgency to form a strategic plantation industry law to increase the added value of plantation products.